Digital Voting Systems - Godapitiya Hewage, Buddhini (My University, 2025)
Digital voting systems represent a significant evolution in the democratic process, offering the potential to improve accessibility, efficiency, and trans- parency in elections. Despite technological advances, widespread adoption remains limited due to concerns about security, usability, and practical de- ployment. This thesis examines three prominent digital voting systems — Helios, Estonian i-Voting, and Voatz — to assess their readiness for large- scale democratic use. The research addresses key questions regarding the security and crypto- graphic robustness, usability and accessibility, and practical deployment char- acteristics of these systems. A qualitative comparative case study method- ology is employed, drawing on published literature, technical documentation, security audits, and real-world deployment reports. Each system is analysed across multiple dimensions, including privacy, integrity, verifiability, coercion resistance, voter experience, infrastructure requirements, and operational per- formance. Findings highlight that while each system demonstrates innovative solu- tions to digital voting challenges, significant trade-offs exist between security, usability, and scalability. Helios provides strong theoretical guarantees and transparency in organizational elections, but practical usability remains a con- cern. Estonian i-Voting demonstrates the feasibility of national-scale internet voting supported by robust digital identity infrastructure, yet concerns about coercion and system transparency persist. Voatz illustrates the potential of mobile blockchain-based voting but faces critical security vulnerabilities and limited public trust. This study contributes a systematic, multi-dimensional comparison of dig- ital voting systems, providing insights for policymakers, election administra- tors, and researchers. By evaluating existing implementations in terms of security, usability, and deployment readiness, the thesis informs future devel- opment and adoption strategies for digital voting technologies.
Keywords: Keywords: Digital Voting, E-Voting Systems, Helios, Estonian i-Voting, Voatz.